2009
DOI: 10.1159/000221837
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of Photodynamic Therapy for Typical Age-Related Macular Degeneration and Polypoidal Choroidal Vasculopathy: A Multicenter Study in Hyogo Prefecture, Japan

Abstract: Purpose: We aimed to evaluate the effects of photodynamic therapy (PDT) on different phenotypes of age-related macular degenerations (AMD): typical AMD (tAMD) and polypoidal choroidal vasculopathy (PCV). Procedures: 246 eyes from 242 patients (tAMD: 139, PCV: 107 eyes) were recruited. Gender, age, best-corrected visual acuity (BCVA) before treatment, greatest linear dimension before treatment, lesion phenotype and PDT frequency were evaluated for predicting the BCVA at 12 months after PDT using stepwise multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 57 publications
(40 reference statements)
1
27
0
Order By: Relevance
“…Most studies quoted 1-year avoidance of moderate visual loss of more than 80% and three-line visual improvement of 25-55%. The response of PCV to PDT is significantly better than CNV in both visual acuity 27 and electrophysiology outcome, 28 especially among cases presenting with serous PED. 29 However, clinical experience suggests that a subgroup of PCV patients respond poorly to verteporfin PDT monotherapy.…”
Section: Treatmentmentioning
confidence: 99%
“…Most studies quoted 1-year avoidance of moderate visual loss of more than 80% and three-line visual improvement of 25-55%. The response of PCV to PDT is significantly better than CNV in both visual acuity 27 and electrophysiology outcome, 28 especially among cases presenting with serous PED. 29 However, clinical experience suggests that a subgroup of PCV patients respond poorly to verteporfin PDT monotherapy.…”
Section: Treatmentmentioning
confidence: 99%
“…PCV is often found in the extramacular area, whereas tAMD always exists within the macular area [7,8]. In addition, the natural course and response to treatment are often different between tAMD and PCV [9,10,11,12,13,14,15,16,17]. Moreover, recent genetic studies suggested a possible difference in the genetic background between tAMD and PCV [18,19,20,21,22,23,24,25], as well as the existence of heterogeneity among PCV cases [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…However, they failed to demonstrate an association of the Y402H variants in CFH with the lesion size in AMD or PCV [32]. Therefore, the initial lesion size, which may influence the response to PDT [8], was unlikely to be responsible for the outcome of PDT associated with the CFH variants. In fact, we did not find any difference in the initial GLD between PDT responders and non-responders in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…PCV is known to have a better response to photodynamic therapy (PDT) than typical neovascular AMD, but the reason for this is not understood [7,8]. Moreover, there is some heterogeneity in the response to PDT among PCV patients [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation